Evaluation of Boot Camps for Juvenile Offenders in Cleveland, Denver, and Mobile, 1992-1993 - Bourque, Blair B. ([Verlag nicht ermittelbar], 1999)
Boot camps, a popular alternative to standard correctional facilities, are characterized by a strong emphasis on military structure, drill, and discipline and by an abbreviated period of incarceration. In 1990, the Office of Juvenile Justice and Delinquency Prevention (OJJDP) launched a demonstration program to develop boot camp models for juveniles and to test the feasibility and appropriateness of their implementation. In September 1991, three groups received awards to develop and implement boot camps as intermediate sanctions: the Cuyahoga County Court of Common Pleas in Cleveland, Ohio, the Colorado Division of Youth Services in Denver, Colorado, and the Boys and Girls Clubs of Greater Mobile, Alabama. Simultaneously, the National Institute of Justice sponsored an evaluation of the implementation of the demonstration programs, focusing on the experiences of youths who entered the program during the first year of operation, from 1992 to 1993. This collection contains data from the program evaluation conducted on these three boot camps during the first year. The core of the assessment was a management information system that captured administrative data as the offenders progressed through the demonstration program. At intake, researchers collected demographic, criminal, and family and social information. Demographic information collected at intake includes age, race, education, and employment. Criminal data covers criminal history, current offense, and case information, while family and social history variables include whether the youths' parents had a criminal record, whether their family received public assistance, and whether they had delinquent friends, delinquent siblings, discipline problems at home or school, or a history of psychological problems. At the beginning and end of the boot camp term, staff rated the youths' performance on educational and behavioral measures. The youths were also surveyed about the rules of boot camp, their opinions of instructors, and their self-esteem, drug and alcohol use, and criminal behavior. At the end of the first 90 days (the residential period), data were collected on the date of graduation, infractions during boot camp, honors or awards, and special services received. Five months after graduation, youths were evaluated on their aftercare experiences. Some sites supplemented the basic management information with data collected on educational performance, employment history and expectations, physical fitness, and youth attitudes.